EVALUATION OF ECONOMIC EFFICIENCY OF AIRCRAFT OPERATING LEASING - Юн, Г. М.; Кабаніхіна, К. В. (Proceedings of National Aviation University (archive), 2021)
The issue of restoring the airline’s fleet through aircraft leasing was considered. An economic-mathematical model for assessing the economic efficiency of operating leasing is proposed.